Prospecção de óleos essenciais para o controle de Spodoptera frugiperda (Lepidoptera: Noctuidae) e seletividade à Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) - Sombra, Kássio Ewerton Santos (2019)
The essential oils of aromatic plants, with insecticidal, repellent or phage-inhibiting activity, have been highlighted as alternatives to the control of pest arthropods. With varied composition, they can act on multiple sites of action, reducing the possibility of occurrence of resistance and, in some cases, presenting selectivity to natural enemies, as parasitoids. The objective of this work was to evaluate the insecticidal, repellent and antifeedant potential essential oils of pepper-rosemary Lippia sidoides Cham. (Lepidoptera: Noctuidae), citronella Cymbopogon winterianus Jowitt (Poaceae) and lemongrass Cymbopogon citratus (DC) Stapf (Poaceae) on fall armyworm, Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) and, the selectivity to the egg parasitoid, Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae). Ovicidal, larvicidal and pupicidal activities per contact were evaluated, calculating lethal dosages (LD50). Besides the repellency; antifeedant, using the methods of the foliar discs with and without possibility of choice; and antibiosis, incorporating the oils into the artificial diet. The selectivity was evaluated by the survival and parasitism of T. pretiosum. The three essential oils showed insecticidal activity on eggs, larvae and pupae of S. frugiperda, with the rapid action of pepper-rosemary oil solutions (mean 97.4% ovicidal potential, 74.2% pupicide, plus LD50 of only 0.001% and 0.033%, by exposure and topical application, respectively). The oils also showed repellency, antifedance and antibiosis, especially the lemongrass oil with 54.0% of repellency at 0.1% and that of pepper-rosemary with LD50 by antibiosis of 0.151% and antifeedant potential of 49.0%. The citronella oil presented insecticidal activity, repellent, antifeedant and antibiosis in a longer period, in some parameters, it was compared to the control. Pepper-rosemary oil showed to be more selective, with LD50 of 0.43% on adults of T. pretiosum, reducing only 22% of parasitism, and inferring 88% of emergence when at 0.01%, considered innocuous. While citronella and lemongrass oils were considered slightly harmful in most of the dosages evaluated. The multiple activities and the selectivity of the essential oils may allow integration (not coincidentally) with releases of T. pretiosum in the integrated management of the fall armyworm.